Switching From Daily DPP-4 Inhibitor to Once-Weekly GLP-1 Receptor Activator Dulaglutide Significantly Ameliorates Glycemic Control in Subjects With Poorly Controlled Type 2 Diabetes Mellitus: A Retrospective Observational Study - Sanada, Junpei; Kimura, Tomohiko; Shimoda, Masashi; Tomita, Akiko; Fushimi, Yoshiro; Kinoshita, Tomoe; Obata, Atsushi; Okauchi, Seizo; Hirukawa, Hidenori; Kohara, Kenji; Tatsumi, Fuminori; Nakanishi, Shuhei; et al. (Frontiers in Endocrinology, 2021)
Aim. ₋ At present, daily DPP-4 inhibitors are quite frequently prescribed in subjects with type 2 diabetes mellitus (T2DM). Recently, it has been drawing much attention that once-weekly incretin-based injection dulaglutide was developed. In this study, we aimed to examine the possible effects of once-weekly GLP-1 receptor activator (GLP-1RA) dulaglutide on glycemic control as well as various metabolic parameters. Methods. ₋ We made a direct comparison between the effect of daily DPP-4 inhibitor and once-weekly dulaglutide on glycemic control in “study 1 (pre-post comparison)” and set control group using propensity score matching method in “study 2”. Results. ₋ In study 1, switching from daily DPP-4 inhibitor to dulaglutide significantly ameliorated glycemic control in subjects with T2DM. Such effects were more obvious in poorly controlled subjects. After 1:1 propensity score matching, switching group improved glycemic control compared with non-switching group in study 2. Conclusion. ₋ We should bear in mind that switching from daily DPP-4 inhibitor to once-weekly GLP-1RA dulaglutide exerts more favorable effects on glycemic control regardless of age, body weight and duration of diabetes in subjects with T2DM, especially when we fail to obtain good glycemic control with daily DPP-4 inhibitor.